2002
DOI: 10.1139/v02-098
|View full text |Cite
|
Sign up to set email alerts
|

Enzymatic oxidation of cyclopropylbenzene: structures of new metabolites and possible mechanistic implications

Abstract: Cyclopropylbenzene was subjected to whole-cell fermentation with either Escherichia coli JM109 (pDTG601) or E. coli JM109 (pDTG602), expressing toluene dioxygenase and toluene dioxygenase – dihydrodiol dehydrogenase enzymes, respectively. The corresponding metabolites, 3-cyclopropylcyclohexa-3,5-diene-1,2-diol (3) and 3-cyclopropylbenzene-1,2-diol (5) have been isolated in yields of 2.5 and 1 g L–1, respectively. The absolute stereochemistry correlation for 3 is provided, along with a preliminary discussion of… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
11
0

Year Published

2003
2003
2016
2016

Publication Types

Select...
4
1

Relationship

2
3

Authors

Journals

citations
Cited by 12 publications
(11 citation statements)
references
References 21 publications
0
11
0
Order By: Relevance
“…Cyclopropylbenzene, previously investigated in connection with the mechanism of the enzymatic oxidation, 5 has proven to be an excellent substrate for the enzyme. We prepared the cyclopropylarenes 6 Table 1 and subjected them to the whole-cell fermentation protocol.…”
Section: Resultsmentioning
confidence: 99%
See 1 more Smart Citation
“…Cyclopropylbenzene, previously investigated in connection with the mechanism of the enzymatic oxidation, 5 has proven to be an excellent substrate for the enzyme. We prepared the cyclopropylarenes 6 Table 1 and subjected them to the whole-cell fermentation protocol.…”
Section: Resultsmentioning
confidence: 99%
“…In all cases, the absolute configuration was proven by comparison with synthetic material derived from diol 15, whose absolute stereochemistry has already been firmly established, 7 with the exception of metabolite 8, whose match was made with the known diol 23. 8 Oxidation of racemic trans-cyclopropylstilbene gave diene diols 12a and 12b, which was reduced with potassium azodicarboxylate/acetic acid and the diol protected as an acetonide, 5 to provide 20a and 20b (Scheme 1). 1 H and 13 C NMR spectroscopic data for compounds 20a and 20b revealed an approximate 1:1 ratio of diastereoisomers.…”
Section: Listed Inmentioning
confidence: 99%
“…17 Diol 2, unlike 3, is quite robust, probably because of the electron flow from the two functionalities is mutually cancelled and does not contribute to the lability of either hydroxyl. Electrochemical reduction 18 of 2 at À2.7 V (Hg cathode) gave 3, which was immediately subjected to diimide reduction with potassium azodicarboxylate (PAD) 19 and subsequently protected as the silyl ether 11. Initial attempts to determine the absolute configuration of diol 2 were performed according to the precedent for vinyl halides to undergo substitution by sulfur nucleophiles by a putative addition-elimination mechanism mediated by HMPA.…”
Section: Resultsmentioning
confidence: 99%
“…Racemic cis-dihydroxy cyclohexane was converted to a monothexyl derivative and further transformed to MosherÕs ester 12, whose 19 F NMR spectrum displayed signals of equal intensity at À71.8 and À72.6 ppm. Both samples of 9 were converted to their Mosher esters and their 19 F NMR spectra displayed a single signal at À72.8 ppm. On the basis of this evidence we concluded that 2 possesses the b-absolute configuration as indicated in Scheme 1.…”
Section: Resultsmentioning
confidence: 99%
“…8 Also, results concerning the side chain modification of cis-diols on previously functionalized rings have been reported. [9][10][11][12][13][14][15] 0040-4039/$ -see front matter Ó…”
Section: Introductionmentioning
confidence: 99%